Detection of membrane-bound and soluble antigens by magnetic levitation. Issue 20 (14th September 2017) - Andersen, Mikkel Schou; Howard, Emily; Lu, Shulin; Richard, Matthew; Gregory, Mark; Ogembo, Gordon; Mazor, Ofer; Gorelik, Pavel; Shapiro, Nathan I.; Sharda, Anish V.; Ghiran, Ionita
Abstract : Magnetic levitation is a technique for measuring the density and the magnetic properties of objects suspended in a paramagnetic field. Abstract : Magnetic levitation is a technique for measuring the density and the magnetic properties of objects suspended in a paramagnetic field. We describe a novel magnetic levitation-based method that can specifically detect cell membrane-bound and soluble antigens by measurable changes in levitation height that result from the formation of antibody-coated bead and antigen complex. We demonstrate our method's ability to sensitively detect an array of membrane-bound and soluble antigens found in blood, including T-cell antigen CD3, eosinophil antigen Siglec-8, red blood cell antigens CD35 and RhD, red blood cell-bound Epstein–Barr viral particles, and soluble IL-6, and validate the results by flow cytometry and immunofluorescence microscopy performed in parallel. Additionally, employing an inexpensive, single lens, manual focus, wifi-enabled camera, we extend the portability of our method for its potential use as a point-of-care diagnostic assay.